Decentralization, healthcare access, and inequality in Mpumalanga, South Africa. (May 2018) - Winchester, Margaret S.; King, Brian
Abstract: Healthcare access and utilization remain key challenges in the Global South. South Africa represents this given that more than twenty years after the advent of democratic elections, the national government continues to confront historical systems of spatial manipulation that generated inequities in healthcare access. While the country has made significant advancements, governmental agencies have mirrored international strategies of healthcare decentralization and focused on local provision of primary care to increase healthcare access. In this paper, we show the significance of place in shaping access and health experiences for rural populations. Using data from a structured household survey, focus group discussions, qualitative interviews, and clinic data conducted in northeast South Africa from 2013 to 2016, we argue that decentralization fails to resolve the uneven landscapes of healthcare in the contemporary period. This is evidenced by the continued variability across the study area in terms of government-sponsored healthcare, and constraints in the clinics in terms of staffing, privacy, and patient loads, all of which challenge the access-related assumptions of healthcare decentralization. Highlights: South Africa's ongoing healthcare decentralization policies reshape access to care. Local health dynamics in Mpumalanga are spatially and historically produced. Policy rollout should consider local variation in experience.